The effect of uterine artery embolization on fertility preservation in the treatment of symptomatic uterine fibroids - Zapała, Magdalena; Środoń, Agnieszka; Łapaj, Monika; Wilk, Joanna; Cholewa, Małgorzata Maria; Chyćko, Małgorzata; Kromer, Agata; Cichoń, Katarzyna; Gawryś, Agnieszka; Czarnota, Julia (Journal of Education, Health and Sport, 2023)
Introduction: Uterine fibroids are the most common benign tumors of the uterus. Most often they are asymptomatic, but in their course there may be ailments such as: abnormal bleeding, anaemia, pain, constipation, problems with urination. These tumors are also one of the many causes of infertility. They are most often detected during a standard ultrasound examination. Pharmacological, minimally invasive and surgical treatment is currently available. Aim: The aim of our study was to review scientific articles in order to demonstrate whether the treatment of uterine fibroids with uterine artery embolization has an impact on fertility and pregnancy outcomes. Materials and methods: Review of the latest PubMed literature, Google Scholar in the period 2017 - 2023 and evaluation of available randomized controlled trials using uterine artery embolization in terms of fertility preservation by assessing ovarian reserve, number of pregnancies, miscarriages and perinatal complications. Conclusions: Uterine artery embolization is a safe and effective method in reducing symptoms associated with uterine fibroids. This procedure shortens hospitalization and recovery time compared to myomectomy or hysterectomy. Unfortunately, for women who want children, this method is not recommended due to the risk of reduced ovarian reserve and miscarriage, premature birth, placental abnormality, and severe postpartum hemorrhage.